SIKAP BAHASA PEMBACA TANDA TERHADAP BAHASA JEPANG DALAM LANSKAP LINGUISTIK LITTLE TOKYO BLOK M - Syahid, Abdurrahman (UI Scholars Hub, 2025)
The use of a language in a linguistic landscape outside its native environment tends to evoke attitudinal stances among individuals in the society. This phenomenon can be observed across Little Tokyo Blok M, Jakarta where Japanese language is widely used on restaurant signs. This master thesis discusses the language attitude of sign readers toward the utilization of Japanese in the area to identify the emerged language attitude and to explain the influencing factors. The study is conducted in mixed methods. The quantitative method (societal treatment approach) examines the statistics of language signs found in Japanese restaurant in regards to their multilingualism and code preference. On the other hand, the qualitative method (direct approach) explores the visitors’ responses during sosiolinguistic interviews to understand the cognitive process behind their attitude. The results show that the language attitude toward Japanese as a foreign language in the Little Tokyo is positive in nature. The positivity is reflected both on the triadic components of the attitude and across the various contexts of signage. Further, the notions of exoticism and authenticity concerning Japanese and its associations are found to be the influencing factors in two different parts of the attitude formation process. Contrary to the existing cognitive model, those parts are found to work simultaneously in determining the characteristics of the language attitude. Bringing forth empirical novelty and theoretical challenge, this thesis could serve as a valuable foundation or reference for further studies.